Incidental pancreatic cystic neoplasms in an asymptomatic healthy population of 21, 745 individuals: Large-scale, single-center cohort study. Issue 51 (December 2016) - Chang, Ye Rim; Park, Joo Kyung; Jang, Jin-Young; Kwon, Wooil; Yoon, Jeong Hee; Kim, Sun-Whe
Abstract : Abstract: Although incidental pancreatic cystic neoplasms are being diagnosed with increasing frequency, little is known about the accurate prevalence of pancreatic cysts in the general population. The aims of this study were to evaluate the crude prevalence rate of pancreatic cystic neoplasms in asymptomatic healthy adults, and calculate the age- and sex-adjusted nationwide prevalence rate. A total of 21, 745 asymptomatic individuals who underwent abdominal computed tomography (CT) as a health screening examination were enrolled between 2003 and 2013 at the Seoul National University Hospital Healthcare System Gangnam Center. Nationwide population data of 2010 were collected from the National Statistical Office, Korea. Incidental pancreatic cystic neoplasms were found in 457 individuals whose mean age was 58.7 years. The types of neoplasms were reviewed by 2 separate designated radiologists and the final diagnosis was made as follows: intraductal papillary mucinous neoplasm: 376 (82%), serous cystic neoplasm: 19 (4%), mucinous cystic neoplasm: 7 (2%), and indeterminate cysts: 55 (12%). Eight cases underwent operation. The crude prevalence rate was 2.1% and the age- and sex-adjusted expected nationwide prevalence was 2.2%. The prevalence increased with age. Here, we reported the first large-scale study among the healthy population to find out the prevalence rate of pancreatic cystic neoplasms; the age- and sex-adjusted prevalence was 2.2%, and increased with age. Further investigations regarding the clinical implications of incidental pancreatic neoplasms are necessary.